PENGETAHUAN, SIKAP, DAN DUKUNGAN TEMAN SEBAYA BERHUBUNGAN DENGAN KEBERSIHAN DIRI SAAT MENSTRUASI PADA REMAJA PUTRI DI PONDOK PESANTREN - Legina Anggraeni; Dinni Randayani Lubis; Lia Nurdini (JURNAL KESEHATAN REPRODUKSI, 2023)
Abstract Background: Undergoing menstruation cleanly and safely is a human right for every woman, including young women. Young women who attend Islamic boarding schools tend to behave less well in maintaining personal hygiene during menstruation so that they have the opportunity to get diseases related to the reproductive system. Purpose: This study examined the relationship between knowledge, attitudes, and peer support on personal hygiene behavior among young women at Islamic boarding schools during menstruation. Methods: The research was conducted at Islamic boarding schools in Bogor Regency in August-October 2022, while the design used was cross-sectional. Samples were obtained using a purposive sampling technique with a sample size of 124 young women. The univariate analysis determined the frequency distribution of independent (knowledge, attitude, peer support) and dependent (personal hygiene behavior). In contrast, bivariate analysis using chi-square was performed to determine the relationship between the independent and dependent variables. Results: The results showed that the hygiene behavior of young girls was classified as not good (20.1%), and the results of the chi-square test showed that there was a significant relationship between knowledge (p-value = 0.0001; OR = 8.0; 95% CI: 3.13 - 20.44), attitude (p-value = 0.0001; OR = 6.83; 95% CI: 2.47 - 18.85) and peer support (p-value = 0.0001; OR = 4.97; 95% CI: 2.19 - 11.29) with adolescent personal hygiene behavior during menstruation. Conclusion: Knowledge, attitudes, and peer support received by young women have a significant relationship with personal hygiene behavior during menstruation. Menstrual hygiene management needs to be given continuously by the pesantren to female students (girls). Keywords: Knowledge, Attitudes, Peer Support, Personal Hygiene Behavior, Menstruation   Abstrak Latar belakang: Menjalani menstruasi dengan bersih dan aman merupakan hak asasi bagi setiap perempuan termasuk remaja putri. Remaja putri yang bersekolah di Pondok Pesantren cenderung untuk berperilaku kurang baik dalam menjaga kebersihan diri saat menstruasi sehingga memiliki peluang untuk terkena penyakit yang berhubungan dengan sistem reproduksi. Tujuan: Penelitian ini bertujuan untuk melihat hubungan pengetahuan, sikap dan dukungan teman sebaya terhadap perilaku kebersihan diri saat menstruasi pada remaja putri di Pondok Pesantren. Metode: Penelitian dilaksanakan pada Pondok Pesantren di Kabupaten Bogor pada bulan Agustus-Oktober 2022, sedangkan desain yang digunakan adalah cross sectional. Sampel didapatkan menggunakan teknik purposive sampling dengan jumlah sampel sebesar 124 remaja putri. Analisa univariat dilakukan untuk mengetahui distribusi frekuensi variabel independen (pengetahuan, sikap, dukungan teman sebaya) dan dependen (perilaku kebersihan diri) sedangkan analisa bivariat menggunakan chi-square dilakukan untuk mengetahui hubungan antara variabel independen dan variabel dependen. Hasil: Hasil penelitian menunjukan perilaku kebersihan remaja putri tergolong kurang baik (20,1%) dan hasil uji chi-square menunjukan adanya hubungan yang bermakna antara pengetahuan (p-value = 0,0001; OR = 8,0; CI 95%: 3,13 - 20,44), sikap (p-value = 0,0001; OR = 6,83; CI 95%:  2,47 – 18,85) dan dukungan teman sebaya (p-value = 0,0001; OR = 4,97; CI 95%: 2,19 - 11,29 ) dengan perilaku kebersihan diri remaja saat menstruasi. Kesimpulan: Pengetahuan, sikap dan dukungan teman yang diterima oleh remaja putri memiliki hubungan yang signifikan dengan perilaku kebersihan diri saat menstruasi. Manajemen kebersihan menstruasi perlu diberikan terus menerus oleh pihak pesantren kepada santriwati (remaja putri). Kata kunci: Pengetahuan, Sikap, Teman Sebaya, Perilaku Kebersihan Diri, Menstruasi